DEVELOPMENT OF ADVANCED MONITORING SYSTEM FOR IOT-BASED RAW WATER QUALITY PREDICTION - Sari, Asri Fornika; Panjaitan, Seno Darmawan; Sanjaya, Bomo Wibowo; Saleh, Muhammad; Priyatman, Hendro (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The availability of clean water is a fundamental need for every individual, and PERUMDA Air Minum, has an important role in meeting this need in Indonesia. Water quality has a great influence on human health, so it cannot be ignored. This research developed an Internet of Things (IoT)-based raw water quality monitoring device for PERUMDA Air Minum Tirta Khatulistiwa Pontianak using a Raspberry Pi Pico W microcontroller. This device enables real-time monitoring, overcomes limitations in manual water quality monitoring, and provides remote monitoring access through the Blynk application. In addition, this research also implements the ARIMA method to predict the pH, temperature, and turbidity values of raw water in the sedimentation basin within the next seven days to support planning and treatment steps for raw water. The development of this tool aims to improve monitoring efficiency and proactive response to changes in water conditions, with the hope of being able to maintain clean water supply more effectively and overcome the constraints of manual monitoring. The results showed that the Mean Absolute Percentage Error (MAPE) of the performance of the constructed PDAM water quality monitoring device was 0,58%, while the MAPE of the predicted performance was 5,88%.